A Novel Mouse Model of Liver Ischemic/Reperfusion Injury and its Differences to the Existing Model. (3rd September 2015) - Zhang, Jianjian; Zhang, Ming; Zhang, Jianjun; Xia, Qiang
ABSTRACT: Background: Ischemia of the cephalad lobes (70% of liver mass) is a frequently employed mouse hepatic ischemia/reperfusion (I/R) model that does not involve outflow occlusion. This model produces results with relatively large variances. Materials and Methods: A novel model of ischemia of the left lateral lobe (35% of liver mass) that involves temporarily occluding the blood supply to the cephalad lobes to expel blood followed by occlusion of both the inflow and outflow of the left lateral lobe, was developed. Mice in the 35% (novel) and 70% (existing) model groups were subjected to I/R injury, and biochemical and histological analyses of blood and liver samples were performed. Tissue oxygen partial pressure (tPO2 ) measurements in the ischemic lobes were also performed to determine whether the hepatic tissue was in a stable hypoxic state. Statistical analyses of the biochemical results, histological scores, and tPO2 levels were performed from which coefficients of variation (CV) were calculated. Results: The CVs of the aminotransferase activities, histological scores, and tPO2 levels were much lower in the 35% group than those in the 70% group. The tPO2 measurements demonstrated that inflow occlusion in the 70% model did not result in a stable hypoxic state, even after the portal triads were ligated and severed, indicating that there was blood reflux from the vena cava, which would be responsible for the variations in results with the 70% I/R model. Conclusions: The new 35% I/R model leads to reproducible results because both inflow and outflow of the ischemic lobe are occluded.